Mechanical Performance of Prefabricated Assembly Air Ducts Subject to Assembly and Grouting Defects - Bao, Shufeng; Zhang, Jinwen; Zhang, Yongxing (Buildings (Basel), 2025)
This paper presents an investigation into the mechanical performance of a subway station prefabricated assembly air duct (PAAD), constructed by assembling the prefabricated reinforced concrete segments. The study is implemented through numerical analysis, focusing on the impact from the grouting defects in the sleeve grouting connection and assembly error defects along the assembly direction. The results demonstrate that the assembly error defect has almost no impact on the mechanical performance of the PAAD, satisfying the safety requirements for use. However, the grouting defects in the sleeve grouting connection can influence the mechanical performance of the PAAD, in which the maximum tensile stress of concrete in the sleeve grouting connection with a 20 mm-long bottom grouting defect is greater than the tensile strength of that concrete, and strengthening treatment is thus required for ensuring the structure’s safety and reliability. This study provides the basis for applying a PAAD in subway station construction.